ANTARA “IDE KEMAJUAN” KOLONIAL DAN REALITAS LINGKUNGAN: JALAN RAYA DALAM PEMBANGUNAN PRASARANA PERHUBUNGAN DI PESISIR BARAT KALIMANTAN - Any Rahmayani; Dana Listiana (Balai Pelestarian Nilai Budaya Kalimantan Barat, 2022)
This paper aims to find out the considerations of the colonial government in building transportation infrastructure to facilitate economic exploitation on the west coast of Kalimantan. For this reason, this paper questions road construction as the only option for the colonial government when faced with the idea of constructing a railway which at that time was the latest trend in land transportation and the environmental realities that had been built, namely waterway. The problem was studied using the historical method with an urban studies approach. The result shows that road construction that is “a middle ground” is in line with “the idea of progress” that was emerging in the Nederland Indies in the context of the New Order (the New Colonial World). The “ideas” consisting of expansion, efficiency, and welfare are detected from (1) the embryo of a coastal road that has been developed since the second half of the 19th century, (2) pacification and supervision for coastal areas which were the former centers of the Kongsi Wars, (3) optimization of economic connectivity, and (4) development of alternative roads.